2019
DOI: 10.1017/jfm.2019.609
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory flow regimes around four cylinders in a diamond arrangement

Abstract: Oscillatory flow around a cluster of four circular cylinders in a diamond arrangement is investigated using two-dimensional direct numerical simulation over Keulegan–Carpenter numbers (KC) ranging from 4 to 12 and Reynolds numbers (Re) from 40 to 230 at four gap-to-diameter ratios (G) of 0.5, 1, 2 and 4. Three types of flows, namely synchronous, quasi-periodic and desynchronized flows (along with 14 flow regimes) are mapped out in the (G, KC, Re)-parameter space. The observed flow characteristics around four c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The spanwise averaged cross-sectional flow fields (not shown here) are similar to their counterparts obtained from 2-D DNS. This observation is consistent with previous findings in literature of oscillatory flow past cylinder(s)[14,[16][17][18]. Since the primary objective of this study is on CD and CM and 3-D simulations at high β constitute a daunting task computationally, the following discussions are based on the results from 2-D DNS.…”
supporting
confidence: 88%
“…The spanwise averaged cross-sectional flow fields (not shown here) are similar to their counterparts obtained from 2-D DNS. This observation is consistent with previous findings in literature of oscillatory flow past cylinder(s)[14,[16][17][18]. Since the primary objective of this study is on CD and CM and 3-D simulations at high β constitute a daunting task computationally, the following discussions are based on the results from 2-D DNS.…”
supporting
confidence: 88%
“…Previous studies (e.g. Ren et al 2019) have shown that the stroboscopic view of flow fields sampled at the higher frequency over the entire period of the low frequency constitutes an effective way of revealing the physical mechanism of quasi-periodic oscillation. The regular vortex shedding frequency St 1 ≈ 0.0982 is used as the sampling frequency over the secondary period in the following flow visualisations.…”
Section: Quasi-periodic Sheddingmentioning
confidence: 99%
“…This method has been applied in the community of fluid mechanics to elucidate the synchronisation behaviours of quasi-periodic phenomena in self-excited jets (Li & Juniper 2013), thermoacoustic systems (Kashinath, Li & Juniper 2018) and bluff-body flows (Ren et al. 2019; Konstantinidis et al. 2020; Aswathy & Sarkar 2021) and demonstrated to be effective in revealing the nature of flows that involves complex interactions.…”
Section: Methodsmentioning
confidence: 99%